Tradisi Ontalan di Madura: Perspektif Hukum Syafi’i dalam Pernikahan Islam - Alwy, Subadar (Al-Inṣāf, 2024)
Ontalan is a tradition deeply rooted in Madurese culture and is carried out in the context of wedding celebrations. The term "ontalan" originates from the Javanese word "oncal," which means to perform the act of throwing, particularly throwing money to the newlyweds as they sit together. As a tradition ingrained in the life and local wisdom of the Blega community, ontalan continues to be upheld as a cultural heritage with crucial social and economic functions. Socially, ontalan serves to strengthen social bonds between families, evolving into a symbol of family unity and an agreement related to the marriage of the prospective couple. Meanwhile, the economic function of ontalan involves contributing to families with intentions and serving as a financial provision for newlyweds embarking on their life together.From the perspective of the Shafi'i school of thought, there is ongoing debate among scholars regarding whether ontalan should be classified as a gift or a debt. Efforts to preserve the ontalan tradition persist, with individuals passing it down to future generations, engaging in development, and making modifications to ensure its continued relevance in line with the changing times.